Digital bonds: patient and therapist factors influence telehealth rapport building in speech-language services - Hao, Ying; Park, Hyejin; Webb, Jaret (Frontiers in Psychology, 2025)
IntroductionRapport building is challenging in pediatric telehealth speech-language services, yet factors influencing it remain unclear. The study specified how patient and clinician factors contributed to the issue.MethodsGenerally, the two disorders reflect different levels of behavioral, sensory, and cognitive challenges, and the two ages index different developmental stages. This study surveyed 207 speech-language pathologists (SLPs) about three aspects (i.e., importance, strategy use, and achievement) of rapport when working remotely with children diagnosed with speech sound disorders (SSD) or autism spectrum disorder (ASD) at two ages (0–3 years, 4–8 years). Clinician factors included clinician age, telehealth experience, and digital literacy.ResultsRegarding patient factors, SLPs rated the ASD group higher importance, more strategy use, but lower achievement than the SSD group. Clinicians reported more strategy use and lower achievement of rapport when serving younger children, but a main effect of patient age was not found in the perceived importance of rapport. Regarding clinician factors, older SLPs tended to place higher importance, use more strategies, and feel more achieved on telehealth rapport than younger SLPs. While SLPs without telehealth experience reported similar levels of strategy use for SSD and ASD groups, those with experience, regardless of the diversity of disorder-age combinations, used strategies more frequently for the ASD group. Finally, digital literacy was significantly related to SLPs’ perceived levels of achievement.ConclusionOverall, these findings underscore the importance of both patient and clinician factors when establishing rapport in telehealth, which may be implicational for other professionals who provide services to individuals with disabilities.